(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
The intention of this work is to reconnaissance the resolution of two rows Weyl module in the partition (6, 4) and skew- shape (6,4)/(1,0) depending on the contracting homotopy